International Jurisdiction in respect of unfair acts with competitors - Espiniella Menéndez, Ángel (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
After presenting the issues of international jurisdiction regarding unfair acts against competitors in section I, in section II the litigation strategies are analyzed, which basically can be of three types: one based on the agreement of the parties; second one based on general rules for any economic matter; and the third one based on specific rules. In section III, these strategies are projected in the different morphology of unfair acts, according to the areas of interest of the injured competitors: their intangible assets, their relationships in the market and their stakeholders (customers, suppliers, workers...). In section IV, and precisely because of this very specific morphology, the bounderies with other jurisdiction rules are analyzed, mainly in matter of contracts, intellectual property and insolvency. The final assessment is that, due to the silence of the jurisdiction rules in respect of unfair competition, we excessively depend on the case law construction of the CJEU, which has lights and shadows.